Sexual advice at a Federal University - Gil, Maria Angélica Aires; Oliveira, Andréa Carla; Gil, Erica Aires (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2018)
Purpose: The incidence of Sexually Transmitted Infections (STIs), a serious health problem, remains very high in Brazil, especially for the Human Immunodeficiency Virus (HIV), which has mobilized governments and the scientific community to control them. Sex education should be the primary means of preventing STIs by adopting strategies tailored to each population. The objective was to analyze the profile of individuals who seek sexual counseling at the Federal University of Rio Grande do Norte (UFRN) in Natal, Rio Grande do Norte state. Methods: The study used a quantitative approach, descriptive longitudinal design, and data collection with proportional stratified sampling, totaling 98 self-reporting questionnaires. Results: Participants exhibited the following profile: the majority were single heterosexual young men with secondary schooling. Thirty participants reported having had only one sexual partner and 81 had never contracted any STIs. Conclusion: It is concluded that the subjects who seek sexual counseling practice safe sex and need to be encouraged to undergo HIV testing.